Using theatre techniques as a tool to enable active learning : searching for a pedagogy to transform spectators into spect-actors - Van Schalkwyk, Mareth (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MDram (Drama))--University of Stellenbosch, 2005.